Kematangan emosi dan perilaku agresi verbal pada remaja di komunitas game online - Shella Caturia Devina; Herlan Pratikto; Suhadianto (INNER: Journal of Psychological Research, 2022)
This study aims to determine the relationship between emotional maturity and verbal aggression behavior in adolescents in online gaming communities. This study uses quantitative research methods. The population of this study amounted to 100 participants, so participants were taken using the saturated sample technique in the online gaming community. The instrument in this study uses an emotional maturity scale that has tested the validity of 34 items with a reliability coefficient of 0.927 and a verbal aggression behavior scale that has been tested for validity to 26 items with a reliability coefficient of 0.920. Data analysis using Rho Spearman. The results of data analysis showed that the correlation coefficient was -0.544 with a significance level of p=<0.001, so there was a negative relationship between emotional maturity and verbal aggression behavior in adolescents in online gaming communities. Based on the results of data analysis, it can be concluded that the higher the emotional maturity possessed by adolescents, the lower the verbal aggression behavior that occurs, and vice versa. Keyword : Emotional Maturity, Verbal Aggression Behavior, Adolescent